Comparison of Ankle Taping and Bracing on Ankle Biomechanics during Landing in Functional Ankle Instability - Gregory Dedrick; Hayley McKelle Ulm; Douglas W. Powell; Brett Windsor (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Lateral ankle sprains are one of the most common injuries in athletics. Injury to lateral ankle ligaments can result in persistent instability of the ankle joint, known as functional ankle instability (FAI). Two methods of treating FAI are ankle taping and ankle bracing. The purpose of this study was to compare the effects of ankle taping and ankle bracing on ankle joint kinematics and kinetics during a landing task. Methods: Seven individuals with FAI and seven healthy controls performed three landing trials in each of three conditions: control, taped and braced. Ground reaction forces and three-dimensional kinematics were collected simultaneously while participants performed single-leg step-off landing trials from a box with a height of 0.6m. Peak ankle joint angles and moments were calculated using customized software. Results: Individuals with FAI produced significantly smaller inversion moments compared to healthy controls (p = 0.006). Ankle stabilization did not significantly alter ankle joint angles, ranges of motion or moments. Discussion: The present findings suggest that individuals with FAI exhibit unique ankle biomechanics independent of ankle stabilization modality. Future research may seek to investigate the multi-joint biomechanical adaptations associated with ankle stabilization in individuals with FAI compared to healthy controls.